1995
DOI: 10.1159/000310569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Treatment Variables on Long-Term Results of Argon Laser Trabeculoplasty

Abstract: Eighty-five eyes of 75 patients were retrospectively followed up for 5 years after argon laser trabeculoplasty. The effects of some treatment and patient variables on the results of trabeculoplasty were assessed. The laser power level or visible burn effect on the chamber angle did not have any statistically significant impact on the success rate or degree of intraocular pressure (IOP) decrease. A statistically significant level was reached by the degree of chamber angle pigmentation and the number of pre-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
4
7
1
Order By: Relevance
“…Eyes completely devoid of trabecular pigmentation were not laser treated. A significantly lower success rate was found in the eyes with sparse pigmentation, in agreement with previous findings (Bergeå 1984;Rouhiainen et al 1995). The baseline IOP in the present investigation was at the same level as in some of the previous studies (Tuulonen et al 1987;Glaucoma Laser Trial 1990;GLTFS 1995), but lower than in others (Elsås & Johnsen 1991;Migdal et al 1994;Bergeå et al 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Eyes completely devoid of trabecular pigmentation were not laser treated. A significantly lower success rate was found in the eyes with sparse pigmentation, in agreement with previous findings (Bergeå 1984;Rouhiainen et al 1995). The baseline IOP in the present investigation was at the same level as in some of the previous studies (Tuulonen et al 1987;Glaucoma Laser Trial 1990;GLTFS 1995), but lower than in others (Elsås & Johnsen 1991;Migdal et al 1994;Bergeå et al 1994).…”
Section: Discussionsupporting
confidence: 92%
“…This risk would be reduced by performing laser as a primary procedure. In addition, it has been found that laser trabeculoplasty seems to be more beneficial when it is used as primary therapy (Tuulonen et al 1985;Rouhiainen et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Patients on lower numbers of medications historically have demonstrated statistically better IOP responses with ALT. 34 In our study, many of our patients were on a larger number of medications, which may have contributed to our high failure rate, although this was not statistically significant (P = 0.870 and P = 0.689 by definitions one and two, respectively). Of the 94 eyes in our study, 25 (27%) were on 1 medication, 27 (29%) were on 2, 17 (18%) were on 3, and 15 (16%) were on 4.…”
Section: Discussionmentioning
confidence: 62%
“…The ability to taper glaucoma medications was another observed benefit. 27 Factors toward success were higher baseline IOP, 19,28-30 pseudoexfoliation, 19,28 black race, 27,31 older age, 19,31 male gender, 32 pseudophakic lens status (versus aphakia), 33 number of pre-laser medications, 34 increased pigmentation, 35 number of treatment spots, 35,36 and treatment in the inferior angle. 27 Parameters such as age and refraction 29 were found to be insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Rouhiainen et al (1995) reported statistically better IOP responses with ALT in patients with lower numbers of glaucoma medication preoperatively. In our study, eyes with lower number of medications did not have a better success rate than eyes with ‡3 medication.…”
Section: Discussionmentioning
confidence: 93%